Evaluation of colloidal stability, kinematic viscosity and flash point of B10 Diesel/Biodiesel blends using nanostructured additives based on Al2O3 and oleic acid - Herrera, Adriana P.; Ojeda, Karina A.; Peñaloza, Andrés D. (CT&F - Ciencia, Tecnología y Futuro, 2017)
Alumina nanoparticles were synthesized by sol-gel method and submitted to thermal treatment at 750 and 1000 °C. X-ray diffraction was used to determine crystal formation with sizes up to 280 nm. To achieve stable suspensions, a nano-additive was mixed with the diesel/biodiesel blends along with oleic acid surfactant to obtain concentrations of nano- additives at 10 and 20 ppm. For this, alumina nanoparticles were firstly mixed with 20 mL of oleic acid by using an ultrasonicator. Then, this mixture was heated at 80°C under constant agitation for 1 hour, and it was subsequently submitted to ultrasound for 30 minutes. Colloidal stability was evaluated according to Deryaguin-Landau-Verwey-Oberbeek (DLVO) theory by analyzing the total interaction energy of the system. Effects on the kinematic viscosity and flash point of the B10 blend were determined according to ASTM D-445 and ASTM D-93 regulations. The application of nano-additives in biodiesel blends showed an increase of the kinematic viscosity from 2.75 cSt to 3.33 cSt at 40°C with 20 ppm of nanoparticles in the B10 blend, while flash point increased from 65 °C to 66 °C. These results could represent a beneficial effect for engines performance due to their better lubricant capacity. On the other hand, fuels with high enough flash point are easy to handle for transportation and storage. Then, the implementation of nano-additives represents a good opportunity for the biofuels industry.